Systematic Literature Review: The Influence of Compensation on Employee Performance in Beauty Clinics in Indonesia - Rakhmat Sigit Widodo; Nur Wening (Riviera Publishing, 2024)
Today's beauty business is starting to be looked at by many business people in Indonesia. We can see this from the many public figures who have decided to enter this business. Currently, many people labeled crazy rich are also pursuing this business, so it can be said that the beauty business is quite promising. This study aims to determine the effect of compensation on employee performance in several beauty clinics in Indonesia. The research method used is a Systematic Literature Review (SLR) 6 (six). Journal articles with a slice of compensation variables and employee performance in beauty clinics were published between 2017 and 2023 (see attachment). From searching articles through Google Shoolar, research rabbit and publish or perish, only six articles were found that contained the desired variables with the object of research on employees in beauty clinics. Searches with the keywords compensation, employee performance, and beauty clinics produce many journal articles for research purposes other than beauty clinics. From this study, it is known that four out of 6 articles are studied that state that compensation affects performance in beauty clinics. This illustrates that, in general, compensation will positively affect employee performance in beauty clinics.